KEDUDUKAN KEJAKSAAN DAN PENGISIAN JABATAN JAKSA AGUNG DALAM SISTEM KETATANEGARAAN INDONESIA - Husin Husaini; Muhammad Afdhal Askar (STAIN Bengkalis, 2020)
The Attorney General's Office of the Republic of Indonesia is a government institution that exercises state power in the field of prosecution and other powers based on law. Attorney General who is the leader and highest person in charge of the prosecutor's office who leads, controls the implementation of the duties and authorities of the prosecutor's office. As a law enforcement agency under the executive power and the position of Attorney General who is appointed, dismissed, and accountable to the President, this state institution is not independent in exercising its authority. This research uses normative legal research. The source of the data used in this thesis is collection through literature research, namely by examining secondary data in the form of books, laws and regulations, papers related to this writing. The results of this study conclude that the public prosecutor's office is in the executive realm to make this institution easy for executive power to intervene. Based on this research, the Attorney General's Office exercises authority related to judicial power, but this institution enters the executive realm and filling the position of Attorney General is the President's prerogative. Therefore, the authors recommend changes to the position of the Attorney General's Office and filling the position of Attorney General with changes to the constitution or changes to the prosecutor's law. This is to create an independent prosecutor's office in exercising its authority free from influence and interference from any power. Keywords: Position and Position, Attorney General's Office and Attorney General, Independent.